El proceso de transición de género: Vivencias de una niña transgénero y su familia, habitantes del municipio de Tuluá - Valle del Cauca (2022)
The present research work consists of describing the experiences of a transgender girl and her family, during the gender transition process in her socio-cultural context, which is the municipality of Tuluá - Valle del Cauca, The research provides information on six (06) people from a family with children in the school stage, made up of two adolescents, an emerging adult, and three middle-aged adults based mainly on the analysis of experiences, emotions and experiences experienced during the transition process. gender of one of its members. To achieve this, a theoretical study was carried out using a variety of concepts to understand how society catalogues, designates and expresses the sense of belonging to the sexes and identities, such as femininity and masculinity, gender identity, sexuality, infancy and childhood, the family and the experiences and emotions that they go through during their transition process. The study has a qualitative, phenomenological methodology with a descriptive scope, developed through a semi-structured interview and life history, with a focus group. The interpretation of the data or information obtained is performed through the content analysis technique. Therefore, the following results are obtained: it demonstrates as main axes of influence in the gender transition process, the family as a direct and primary environment, the social context and its relationship with the experiences that occurred during the process and that, within itself , there are still biases, attributions and prejudices against sexual identity, and finally the personal aspect and the experiences that have been had since the gender transition process were analyzed, 14 finding that family and contextual support have a very significant influence on the person with transgender identity.